Participation in local food projects is associated with better psychological well-being: evidence from the East of England. (8th July 2019) - Bharucha, Zareen Pervez; Weinstein, Netta; Watson, Dave; Boehm, Steffen
Abstract: Background: Studies suggest that local food may contribute to well-being, but do not use standardized measures, or control groups. Methods: An online survey compared participants of local food initiatives ( n = 302) with members of the general population ( n = 157) in terms of scores on standardized measures of well-being and distress. Using hierarchical ordinary least squares regression models, we explored the relationship between participation and well-being via four mediators—nature connectedness, psychological need satisfaction, diet and physical activity. Results: Participants scored higher than non-participants on life satisfaction ( t (346) = 2.30, P = 0.02, ρr = 0.12) and the WEMWBS scale ( t (335) = 2.12, P = 0.04, ρr = 0.10), but differences in psychological distress were insignificant. More actively engaged participants scored higher on positive well-being and longer duration participation was associated with higher life satisfaction and less psychological distress. Finally, we found that participation contributes to psychological need satisfaction, better diet and connection to nature, three known drivers of well-being. Conclusions: Well-being may be a co-benefit of local food initiatives beyond the physical and psychological benefits of growing food. Further research is needed to explore the mediators driving these effects, quantify benefits, and track impacts over time and across different social groups.